Effects of 2,4-DP- P (2,4-Dichlorophenoxypropionic Acid-P) Plant Growth Regulator on Fruit Size and Yield of Star Ruby Grapefruit (Citrus paradisi Osb.) - Bilge Yilmaz; Berken Çimen; Turgut Yesiloglu; Meral Incesu; Muge Uysal Kamiloglu; Muharrem Yilmaz (Turkish Journal of Agriculture: Food Science and Technology)
Star Ruby is the main grapefruit (Citrus paradisi) variety grown in Turkey; however, small fruit size is a common problem in ‘Star Ruby’ grapefruit. Fruit size is a decisive external quality parameter in citrus at the marketing of fresh citrus fruits. Fruit size can be enhanced by several techniques such as girdling and thinning. Various plant growth regulators are known to affect the growth and size of citrus fruit. The objective of the present study was to observe the effects of 2,4 dichlorophenoxypropionic acid-p (2,4-DP-P) on the fruit size, yield and quality of Star Ruby from 20-year-old trees budded on sour orange rootstock in Adana, Turkey in 2007. Four concentrations (50, 100, 150 and 300 ppm) of 2,4-DP-P were applied 8 weeks after anthesis during physiological fruit drop when the mean fruit diameter was 13-15 mm. The results indicated that the application of 2,4-DP-P increased the fruit size of Star Ruby grapefruit without reducing yield. The application had a significant effect on fruit yield except for trees treated with 50 ppm 2,4-DP-P. Compared with the control trees, applications of 2,4-DP-P increased the number of large, commercially valuable Star Ruby (>93 mm, 89-93 mm and 84-89 mm). No effects were determined on fruit internal quality parameters. Thus, the results of the present study revealed that 2,4-DP-P can be used to improve the fruit size of Star Ruby fruitlets during the June drop.